Project-Based Learning for Functional Arabic Writing Materials Development - Ali Ba'ul Chusna; Imam Asrori; Abdul Aziz (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2025)
This research and development aims to describe (1) project-based functional Arabic writing teaching materials, (2) validation results of teaching materials from material experts, linguists, and learning media experts, and (3) the effectiveness of the use of project-based functional Arabic writing teaching materials. The research method used R&D with the ADDIE model. The test subjects in this study were students of the Arabic language education program who were taking the Insha'2' 2 course. The results of this study show that (1) The textbook for writing functional Arabic with the title Maahir fi al-Kitabah al-wadhlifiyah consists of six chapters of functional Arabic writing material. This book was developed through the five stages of the ADDIE model. (analysis, design, development, implementation, and evaluation). (2) The results of expert validation show that the textbooks have good quality and are suitable for use, both in terms of material (92%), language (80%), and learning media (78.77%). (3) The results of the effectiveness test of the use of functional Arabic writing textbooks showed a significant increase in student learning outcomes. This shows that using functional Arabic writing teaching materials has proven effective in improving student learning outcomes.